In vitro selection for drought tolerance in two elite sugarcane (Saccharum spp.) genotypes - MANCHANDA, P; KAUR, A; KUMAR, P; CHOUDHARY, O P; GOSAL, S S (The Indian Journal of Agricultural Sciences, 2014)
Abiotic stresses, especially increased salinization of water resources and global scarcity of water, are the major causes of crop losses world-wide. Therefore, an in vitro study was conducted to observe the effect of osmotic stress induced by an osmoticum, polyethylene glycol (PEG), Mol. Weight 6000 on callogenesis and subsequent regeneration in sugarcane (Sacchaarum spp.) cv. CoJ 83 and CoH 119. Callus induction was observed by placing leaf roll segments (~ 1.5 cm long) of sugarcane cv. CoJ 83 and CoH 119 on solid Murashige and Skoog (MS) medium supplemented with 2, 4-dichlorophenoxyacetic acid (2,4-D; 4 mg/l and 5.5 mg/l for CoJ 83 and CoH 119, respectively) + Kinetin (Kin; 0.5 mg/l) + 560 mg/l proline + 30 g/l sucrose + 8 g/l agar. Subsequent regeneration from callus cultures was observed on solid MS + Kin (0.5 mg/l) medium. Significant callus induction and regeneration was observed in both the varieties, but with the addition of PEG (6000) into the callus induction medium, regeneration efficiency was reduced in both the cultivars. Further, the biochemical parameters like estimation of total soluble sugars and total proline content were also analysed. The results indicated that CoH 119 variety of sugarcane is more tolerant to drought stress as compared to CoJ 83 variety.